Kontekstualisasi Hukum Pidana Islam dalam Pembaruan Hukum Pidana Nasional - Makhrus Munajat (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2015)
However, the actual means of the formalization of the law in Indonesia is still, and will always be, debated regarding whether it should be made legally formal or simply applying Islamic values, by which more emphasis is put on the essence over the form. This study attempts to answer this polemic by discussing the transformation of thought about criminal law in Islam as well as the transformation form of thought about Islamic criminal law in Indonesian context. The objects of this study are thus the norms of Islamic criminal law in terms of offenses and chastisement. The research adopts the theory of mas}lah}ah, and objectification theory, namely the translation of Islamic criminal law into an objective article so that it can be accepted by all Indonesian societies. The transformation of Islamic criminal law is hereby understood as the changes in the enactment of law, regarding not only the crime (jari>mah) but also its chastisement based on their time periods and social contexts. The concepts of jari>mah and chastisement are in fact the interconnections of the core law (al-ah}ka>m al-as}liyyah) which contains prohibitions and complementary law (al-ah}ka>m al-muayyidah) which contains chastisements. The transformation form of Islamic criminal law in Indonesia has been largely manifested in the formulation of the law into objective stipulations that can be accepted by all Indonesians regardless their ethnicities, traditions, culture, and religions. The objectification of Islamic criminal law in Indonesia can therefore be used as the basis for the reformulation of national criminal law by proposing universal values of Islamic law so that it can conform to heterogeneous Indonesian societies notwithstanding its original source, Islam.